Rational Design of Peptide Inhibitor Targeting BRCA1-Associated Protein 1 Through Homology Modeling and Molecular Dynamics Simulation: Rational Design of BRCA1-Associated Protein 1 Peptide Inhibitor - Husain, Syarifuddin; Mohamed, Ruzianisra; Abd Halim, Khairul Bariyyah; Mohd Mutalip, Siti Syairah; Hairuddin, Omar Nafiis (Journal of Tropical Life Science, 2025)
Cancer remains a complex and heterogeneous disease, with the BRCA1-Associated Protein 1 (BAP1) recognized as a tumour suppressor gene playing a vital role in various cellular processes. Interestingly, BAP1 is overexpressed in certain cancers, and inhibition of its ubiquitin C-terminal hydrolase (UCH) domain may offer a promising therapeutic strategy. This study aims to identify the key residues involved in the interaction between ubiquitin and BAP1 and to design peptide inhibitors capable of selectively targeting BAP1’s deubiquitinating activity. A 3D protein model of the BAP1–ubiquitin complex was generated using AlphaFold, followed by molecular dynamics (MD) simulations to identify critical interacting residues. Peptide inhibitors were designed based on the β-turn region of ubiquitin, and molecular docking was performed using the HADDOCK 2.4 server. Based on the result, it was observed that mutating Lys6 and Thr9 to arginine improved binding affinity between the cyclic peptide inhibitors and the BAP1, probably due to the complementary attraction between the positively charged arginine residue and the negatively charged surface electrostatic potential of the BAP1 distal site. MD simulations were conducted to assess the stability and interactions of the BAP1-peptide complexes, showing that the CP3K6R/T9R mutant exhibited the highest average number of hydrogen bonds and the strongest binding affinity. The study suggests that electrostatic interactions and residue-specific mutations can be used to optimise peptide inhibitors for BAP1. The findings support the possibility of developing therapeutic strategies to inhibit BAP1 and suppress tumour progression.